Tracking anemia and its determinants from 2006 to 2016 in India: Insights from the National Family Health Survey-4 - Avula, Rasmi; Nguyen, Phuong Hong; Scott, Samuel P.; Agarwal, Aishwarya; Menon, Purnima (International Food Policy Research Institute, 2018)
This Data Note describes the prevalence of anemia and its determinants (as listed on page 11), and coverage of a set of key interventions targeted at improving anemia. The findings here are based on available data from the National Family Health Surveys in 2005-2006 and 2015-2016. For some indicators, age categories may vary depending on information received from the survey.